An instrument for measuring the science interests of grade school children - Zapata, Asuncion G. (1972)
The purpose of this study was to develop an instrument for measuring science interests of grade school children. Thirty randomly selected grade five children of the Philippine Normal College Laboratory composed the subjects. Thirty real objects appearing in the item-list were prepared and the 30 corresponding pictures were drawn. The findings of the study revealed the reliability of the instrument. The study failed to show the validity of the instrument perhaps due to the fallibility of the variables used. The instrument revealed the nature of the science interests of the grade five pupils.